2016
DOI: 10.1056/nejmoa1600693
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy for the Prevention of HIV-1 Transmission

Abstract: BACKGROUND An interim analysis of data from the HIV Prevention Trials Network (HPTN) 052 trial showed that antiretroviral therapy (ART) prevented more than 96% of genetically linked infections caused by human immunodeficiency virus type 1 (HIV-1) in serodiscordant couples. ART was then offered to all patients with HIV-1 infection (index participants). The study included more than 5 years of follow-up to assess the durability of such therapy for the prevention of HIV-1 transmission. METHODS We randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
953
2
22

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,404 publications
(1,039 citation statements)
references
References 24 publications
12
953
2
22
Order By: Relevance
“…Furthermore, the overall viral suppression rate in this study was 51%. This rate of viral suppression is comparable to other contemporary observational clinical cohort studies (suppression rates of 45%–62%)1, 5, 38 and studies in this region (viral suppression rate of 58%),39 but is lower than observed in more recent registries and clinical trials 40, 41, 42. It is also possible that the PHIV with an ICD were sicker for other reasons, such as concomitant infections/lower CD4 cell count, and therefore more likely to have an ICD discharge.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the overall viral suppression rate in this study was 51%. This rate of viral suppression is comparable to other contemporary observational clinical cohort studies (suppression rates of 45%–62%)1, 5, 38 and studies in this region (viral suppression rate of 58%),39 but is lower than observed in more recent registries and clinical trials 40, 41, 42. It is also possible that the PHIV with an ICD were sicker for other reasons, such as concomitant infections/lower CD4 cell count, and therefore more likely to have an ICD discharge.…”
Section: Discussionsupporting
confidence: 85%
“…HIV/AIDS has remained a public health threat for many decades now, and concerted global efforts have resulted in successful prevention and treatment strategies that are beginning to show success in curtailing the spread and pathogenicity of this disease. Importantly, death rates and new HIV‐1 infections have declined in many regions of the world 3. Despite these advances, HIV‐1 remains a devastating global health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Over half of the people living with HIV‐1 are not receiving treatment, and many infected people are not aware of their infection. In 2015, there were an estimated 36.7 million people living with HIV‐1, and approximately 1 million of these died AIDS‐related deaths 3. Moreover, by compromising the immune system, HIV‐1 increases the morbidity and mortality of other devastating diseases, including tuberculosis4 and malaria,5 which are endemic to regions with a high HIV‐1 prevalence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies such as START 2 and TEMPRANO 3 have indicated that individuals benefit from initiating treatment as soon as they are diagnosed. HPTN 052 4, the PARTNERS study 5, 6 and Opposites Attract 7 have demonstrated that individuals on effective treatment do not transmit HIV to their partners. Additionally, the use of tenofovir co‐formulated with emtricitabine for pre‐exposure prophylaxis adds to the armamentarium of prevention technologies enabling individuals to avoid becoming infected.…”
mentioning
confidence: 99%